La historia de las relaciones internacionales en España: un marco interpretativo - Neila Hernández, José Luis (Estudios de Historia de España, 2017)
The History of the International Relations in Spain as a historiographical discipline has been influenced by a many factors: the own condition of Spain as a small State since the begining of the XIXth Century to the end of the XXth Century; the delay of Spain in its process of modernization in relation to the European and Western patterns; and the evolution of historiography in Spain in the framework of sciences. Likewise, Spanish history and, obviously, the history of its international relations have been determined by the sign of exceptionalism until the last third of the XXth Century, time in which the thesis of ‘normalcy’made its way. In this context the consolidation of the history of international took place and, despite its delay, showed the permeability of Spanish historiography concerning Western historiography.